SKRINING AKTIVITAS ANTIOKSIDAN JAMU SUBUR KANDUNGAN KOMERSIAL - Ahmad, Mujahidin (El-Hayah : Jurnal Biologi, 2015)
Selection of traditional medicine is often considered as a choice since the affordable price and low side effects than chemical drugs. One of the well-known herbal medicine produced and consumed in java is Madura Herbal Medicine (MHM). MHM "Subur Kandungan" is one of the original medicinal products which is widely known in inducing fertility, but has not been scientifically standardized so make this many doubt for its usefulness. With the standardization and scientific assessment, MHM ought to be accepted in the modern medical system as well as lead in increasing both society revenues and public health. MHM "Subur Kandungan" consist of garlic (Allium sativum L.), Sweet Flag (Acorus calamus L.), and Intersection rhizome mango (Curcuma mangga Val.) is widely recognized as efficacious herbal medicine for inducing fertility. To determine the potency of those three plants, these were extracted by ethanol and continued by testing the antioxidant potential (DPPH) both individually and mixed. Assessments of phytochemical and antimicrobial potency were discussed. Test results showed that antioxidant activity represented by DPPH IC50 values of ethanol extract of A. sativum, A. calamus, C. manggaÂ  and a mixture of those are 383.56, 335.68, 32.48, 27.773 Âµg/ml (ppm) respectively. Allium sativum and A.calamus are weak antioxidants as having IC50 in the range of 250-500 ppm, while the C. mangga and a mixture of those have strong antioxidant content as having IC50 of less than 50 ppm. Allegedly due to the high antioxidant content of the content of steroids, phenols, tannins, flavonoids, glycosides, diterpene, triterpenes, and alcaloids in A. calamus, also contains steroids, flavonoids, glycosides, diterpene, triterpenes and alaloids on A. sativum and also the presence of terpenoids as compound intersection primary contained in C. mangga respectively.